Future families diverse forms, rich possibilities - Parke, Ross D. (John Wiley & Sons Inc., 2013)
"Future Families explores the variety of family forms which characterize our contemporary culture, while addressing the implications of these increasingly diverse family units on child development"--Provided by publisher.